Perancangan User Interface Sistem Presensi Universitas Primakara Menggunakan Face Recognition dengan Metode Design Sprint - widyasa, bayu angga (Jurnal Teknologi Terpadu, 2025)
This research aims to design a User Interface for Primakara University's attendance system using face recognition technology with the Design Sprint method. The scope of the research includes designing a User Interface for a facial recognition-based attendance system. The method used is Design Sprint, consisting of five stages: Map & Target, Sketch, Decide, Prototype, and Test. The research resulted in a Prototype of the attendance system User Interface, which was Tested using Maze tools. User experience Testing was conducted using the User Experience Questionnaire Plus (UEQ+). The research concludes that the Design Sprint method is effective in designing a User Interface for an attendance system with face recognition technology. The implications of this research contribute to the development of a more efficient and user-friendly attendance system in higher education environments.